(untitled) (International Journal of Occupational Safety and Health, 2022)
Introduction: The women healthcare workers, besides their role in the promotion, prevention, and protection of health for their patients, are exposed to different types of occupational risk at the workplace. The aim of this study was to explore the types of occupational risk encountered by the women healthcare workers and to assess the health and safety measures implemented for the women healthcare workers. Methods: A cross-sectional study was conducted among one hundred women healthcare workers in Aizawl district, Mizoram, India. A self-structured questionnaire was used to collect data on the respondents’ demographic profile, workplace risks, and safety measures. The Work Safety Scale was used to measure the safety measures and was reframed to suit the study’s context and person correlation was calculated. Results: The results show that women healthcare workers experience a greater number of physical risks at the workplace i.e., back pain, headache, eye problem, loss of appetite and needle syringe injuries which is followed by psychosocial (anxiety, insomnia, abuse by patients, low self-esteem and depression) and reproductive risks (irregular menstrual cycle, stillbirth, low birth weight and cervical cancer). The health and safety measures implemented for the healthcare workers are satisfied with an average mean score of 3.64. The study revealed that no clear regulations and recommendations on safety measures have been developed by healthcare settings. Conclusion: The study concluded that better regulation is needed, required to protect and safeguard the physical, psychological, and reproductive risks that women healthcare professionals encounter at the workplace.